Corporate governance, investor protection, and performance in emerging markets - Klapper, Leora F.; Love, Inessa (Journal of Corporate Finance, 2004)
We use recent data on firm-level corporate governance (CG) rankings across 14 emerging markets and find that there is wide variation in firm-level governance in our sample and that the average firm-level governance is lower in countries with weaker legal systems. We explore the determinants of firm-level governance and find that governance is correlated with the extent of the asymmetric information and contracting imperfections that firms face. We also find that better corporate governance is highly correlated with better operating performance and market valuation. Finally, we provide evidence that firm-level corporate governance provisions matter more in countries with weak legal environments.